Graphics processing units in acceleration of bandwidth selection for kernel density estimation - Andrzejewski, Witold; Gramacki, Artur; Gramacki, Jarosław (Zielona Góra: Uniwersytet Zielonogórski)
The Probability Density Function (PDF) is a key concept in statistics. Constructing the most adequate PDF from the observed data is still an important and interesting scientific problem, especially for large datasets. PDFs are often estimated using nonparametric data-driven methods. One of the most popular nonparametric method is the Kernel Density Estimator (KDE). However, a very serious drawback of using KDEs is the large number of calculations required to compute them, especially to find the optimal bandwidth parameter.
Keywords: bandwidth selection; graphics processing unit; probability density function; nonparametric estimation; kernel estimation